THE PROBLEM OF SELF-AWARENESS IN PRESCHOOL PREPARATION GROUPS THEORETICALLY STUDIED - Akhmedova Feruza (Journals Park Publishing, 2022)
The article presents the opinions of foreign scientists on the role and importance of self-awareness of preschool children, that is, the concept of self.
Keywords: I, concept, child, childhood, awareness, identity, future, consciousness, foreign, scientific research.